Міжнародне відлуння суспільно-політичної кризи 1956 року в Польщі - Антипова, О. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2018)
Стаття присвячена висвітленню позицій та дій різних політичних сил та світової спільноти щодо суспільно-політичних процесів у Польщі середини 50-х років ХХ ст. Здійснений аналіз реакції провідних світових держав на події 1956 р. у Польщі дає підстави стверджувати, що Польський жовтень відіграв значну роль у відносинах між західними країнами та СРСР, а також у певній зміні політики останнього щодо країн соціалістичного блоку. Загалом Польський жовтень послабив міжнародну напругу. На міжнародній арені встановилася певна рівновага сил. Мирне подолання кризи в Польщі розв’язувало проблему стабілізації ситуації у центрі протистояння двох воєнно-політичних блоків. The article is devoted to highlighting the position and actions of various political forces and the world community regarding the socio-political processes in Poland in the mid-1950’s. In world history, 1956 was marked by significant historical events in countries of Europe, Asia, Africa and America. Especially deep changes occurred in the Soviet block. The Polish October (the first socio-political crisis in the Polish People’s Republic) occupies a significant place in the social and political life and in the international relations of the countries of Central and Eastern Europe in the mid-1950 s. The study of the events of 1956 in the Polish People’s Republic as a phenomenon of domestic political and international life becomes particularly relevant due to geopolitical changes in Central and Eastern Europe, which took place at the end of the twentieth century. An analysis of the reaction of leading world powers to the events in Poland suggests that the Polish October played a significant role in relations between the western countries and the USSR, as well as in a certain change of the latter’s policy towards to the countries of the socialist bloc. On the whole, Polish October weakened international tension. A certain balance of power was established on the international scene. The peaceful overcoming of the crisis in Poland solved the problem of stabilizing the situation in the center of the confrontation of the two military-political blocs. A comprehensive analysis of the events of 1956 in Poland indicates a systemic crisis in the countries of the Soviet bloc. The Polish socio-political crisis is not only a top priority in the history of Poland, but also acquired world significance. The peculiarity of Poland’s October is that crisis phenomena, exacerbated within the country and reinforced by foreign policy factors, were resolved peacefully. It was precisely this event that helped to maintain a delicate balance between Western countries and the USSR. For the global world, the Polish events of 1956 did not start the change in the East-West coordinate system, but they significantly influenced the political climate in Europe. The experience of solving international problems accumulated in this period became the basis of the construction of international relations on the European continent, which retained its main features almost until the end of the 1960’s and subsequently found its embodiment in the policy of détente.